Марш обреченных: [роман] / Валерий Рощин - Рощин Валерий Георгиевич (Морской спецназ, 2011)
Экземпляры: РБ (20180130) / Инвентарный номер: 54641 / Цена: 30.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Р 81 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6